Do agri-environmental schemes contribute to high nature value farmland? A case study in Emilia-Romagna (Italy). (December 2015) - Viaggi, Davide; Signorotti, Claudio; Marconi, Valentina; Raggi, Meri
Highlights: An ecological indicator for the measurement of high nature value farmland is introduced. The indicator is split into three components: nitrogen surplus, crops variety and livestock density. An application of the indicator at municipality level is presented for the Emilia Romagna region (Italy). A regression analysis confirms that the presence of organic farming is favouring the high nature value farmland. In the case study it is shown that spatial association in the distribution of the indicator takes place. Abstract: The objective of the paper is to determine whether the agri-environmental schemes included in the rural development programme of Emilia-Romagna (Italy) have played a role in enhancing the nature value of farmland in that region. An indicator is developed for biodiversity friendly farming practices (BFFP) and its level and distribution at the municipality level is measured, using data derived from the two last national agricultural censuses, year 2000 and 2010. Thereafter, the relationship between BFFP and participation in rural development measures is analysed by way of spatial econometric techniques. The main result of the paper are consistent with the expectation that RDPs have an impact on how BFFP changes. However, measures supporting organic farming contribute to the evolution of its distribution in a positive manner, whilst the other measures investigated, such as integrated production, do not. The paper also highlights the fact that these effects have significant spatial correlations.